Comparative Analysis of the Performance of the Thermal Pasteurization System Using Ohmic Heating Method with an Electric Heater on Mango Puree - kurniawan, yudhy; Wardika, Wardika; Sugara, Ferry; Alhamid, Muhammad Idrus; Ardiyansyah, Ardiyansyah (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
This study explains the comparative analysis of performance in the thermal pasteurization system of the ohmic heating method with the electric heater in mango puree. The goal is to find out which thermal pasteurization method is better and more efficient. The method used for this study is to compare the two thermal pasteurization methods from the performance obtained, heating time, electrical power and electricity consumption costs. In the pasteurization process, the product is heated not exceeding 70 oC in the ohmic tube with an electric current on an electrode with a thickness of 4 mm attached to the end of the ohmic tube, while pasteurization of the product electric heater is heated in a double jacket tube equipped with an electric heater. The results of the analysis were obtained for the ohmic heating method the efficiency value was 78%, while for the method with an electric heater the efficiency value was 4%, the heating time of the ohmic heating method is 555 seconds, while the heating time of the electric heater method is 1500 seconds, for electric power in the ohmic heating method is 224.59 watts, while in the electric heater method an electric power of 1730.2 watts is obtained, and the cost of electricity consumption of the ohmic heating method is Rp.1,498.33,-/month, while the electric heater method costs electricity consumption of Rp.31,407.26,-/month.